Towards a baseline for reducing the carbon budget in sugarcane: three years of carbon dioxide and methane emissions quantification - Chalco Vera, Jorge Elias; Acreche, Martin Moises (2018)
Sugarcane straw burning or removal and N fertilization are management practices that modify the input of carbon (C) to the soil affecting greenhouse gases emissions and the potential of the soil for C sequestration. This study aimed to determine the effect of post-harvest straw burning and synthetic N fertilization on the dynamics of CO2 and CH4 fluxes in the sugarcane-soil system of Tucuman, Argentina; it also compared these emissions with those of a native forest and discussed a theoretical soil C balance based on C emissions. Close-vented chambers were used to capture CO2 and CH4 during three consecutive growing seasons. The higher CO2 emissions coincided with the period of high soil and air temperatures and rainfalls. There was not a clear pattern in the dynamics of CH4 flux for all sugarcane treatments, while the native forest consistently captured CH4; however, the cumulative CH4 flows were negligible in term of C mass. Annual cumulative CO2 emissions were 12.4–61.4 and 5.9–51.5% higher (for N-fertilized and unfertilized treatments, respectively) when straw was not burned regarding to the burned treatment. However, C losses -as CO2 emissions- in unburnt treatments were lower than the C input from straw and roots, while C losses in burnt treatments were higher than C input from straw and roots. The soil-sugarcane system of Tucuman has a potential C sequestration estimated of 2.03 Mg of C ha−1 yr−1. The results of this manuscript highlighted the importance of preserving straw as a way to maintain or increase soil organic carbon. They also demonstrated the importance of considering management practices when measuring CO2 fluxes during the crop cycle for determining the soil C balance.